Don't let a "good" crisis go to waste: One-upmanship in local responses to the COVID-19 pandemic - Julian Thomas B. Alvarez; Jahm Mae E. Guinto; Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2021)
Unlike in previous crises, the COVID-19 pandemic has wrought a crisis affecting all population groups, all economic sectors and all jurisdictions in the Philippines, as elsewhere. The impact of the COVID-19 vary across localities, however, partly due to differences in local government responses to the pandemic. Our objective is to examine the patterns in the types and timing of local responses among neighboring local government units (cities) for evidence of oneupmanship among their incumbent leaders (mayors). We assembled data for 25 selected cities and then grouped them into 28 neighborhood clusters. Using three indicators, we measure the immediacy, primacy and distinctiveness of the local responses within each cluster over the period March 2020-March 2021. Of the 28 clusters, we find in 19 (67.9 percent) evidence of oneupmanship consistent with the view that the type and timing of local responses are driven by mayors who wish to signal their talents and abilities. Further, mayors who face greater election competition pressures (low vote margin, many rivals) tend to implement responses ahead or uniquely of others. Thus, some leaders are able to turn the COVID-19 crisis into an opportunity to demonstrate their competence to their constituents, presumably to improve their popularity and re-election prospects.
Keywords: D72; H73; I18; 330; COVID-19 pandemic; local responses; one-upmanship; yardstick competition; Philippines